The Relationships of Attachment Style and Social Maladjustment to Death Ideation in Depressed Women with a History of Childhood Sexual Abuse - Smith, Phillip N. (2011)
OBJECTIVE: Women who experience both depression and a history of childhood sexual abuse are at substantially greater risk for suicide compared to those who experience depression alone. Though psychiatric diagnoses, such as Major Depression and Borderline Personality Disorder, are often considered in the assessment and management of suicide risk, understanding how enduring characteristics interact with contextual factors to result in suicide-related thoughts and behaviors may be more useful for identifying specific targets for intervention. DESIGN: The current study used cross-sectional survey methodology to examine the interaction of attachment orientation and acute social maladjustment as risk factors for death ideation in a sample of women with Major Depression and histories of childhood sexual abuse. RESULTS: Social maladjustment was associated with greater likelihood of endorsing death ideation. Avoidant and anxious attachment orientations moderated the social maladjustment and death ideation associations in some domains. Specifically, work-related social maladjustment was associated with greater odds of death ideation for those with higher levels of attachment avoidance. Parent-role related maladjustment was associated with greater odds of death ideation for those with lower levels of attachment anxiety. CONCLUSIONS: Findings demonstrate strong associations between death ideation and acute social maladjustment, and suggest that death ideation may be specific to certain domains of adjustment for anxious and avoidant attachment styles. Implications for the conceptualization and treatment of patients who report death ideation are discussed.